Postoperative Survival of Patients with Stage IIIa Non-small Cell Lung Cancer - Huihui LIU (Chinese Journal of Lung Cancer, 2013)
Background and objective At present, surgery is advocated for stage IIIa non-small cell lung cancer (NSCLC), and the survival of them is determined by many factors. The aim of this study is to analyze the influencing factors of prognosis for stage IIIa surgical patients. Methods Between March 2002 and October 2012, 151 surgical cases that have postoperative pathological finding of stage IIIa NSCLC with completed followed-up data were received in the Peking Union Medical College Hospital. According to different N stages, 151 patients were divided into T4N0/T3-4N1M0 and T1-3N2M0 stages. Kaplan-Meier survival method was used to calculate the overall survival (OS) and progression-free survival (PFS), and to proceed univariate analysis of survival. Cox regression analysis was used to conduct multivariate analysis. A p-value less than 0.05 was evaluated as statistically significant. Results 151 stage IIIa NSCLC patients had 43 stage T4N0/T3-4N1M0 cases and 108 stage T1-3N2M0 cases. The median OS and PFS of the whole group were 38.9 and 12.9 months respectively. The median OS of stage T4N0/T3-4N1M0 and T1-3N2M0 were 48.7 and 38.9 months. The median PFS of them were 14.9 and 19.8 months respectively. There were no significant differences of OS and PFS between two groups. Univariate and multivariate analysis indicated that postoperative chemotherapy had a significant influence on OS of the surgical patients with stage IIIa NSCLC (P=0.001), and family history of tumor had a significant influence on PFS (P<0.05). The maximum diameter of tumor had a significant influence on PFS only in univariate analysis. Conclusion For stage IIIa NSCLC, postoperative chemotherapy can increase OS and PFS, but postoperative radiotherapy have no benefit on them.